Vocational consciousness of young workers: Comparison between young workers' and employers' opinions - HIROOKA, Shuichi; SANO, Sachiko; MATSUBARA, Toshihiro (Japanese Journal of Administrative Science, 1993)
The purpose of this study is to investigate the vocational conciousness of youngworkers by themselves and opinions by their employers. Two kinds of mailquestionnaire surveys were conducted for workers and employers respectively: 1048 young workers (628 male and 420 female) and 1096 employers providedusable data for this study. Main results are the following; (1) Young male workers have more strong motivation toward their work thanfemale ones. (2) Elder female workers (25-30 age) have more strong motivation toward theirwork than younger workers (18-24 age). (3) Employers support philosophy of traditional Japanese managementsystems more strongly than young workers. This tendency is observed as morepopular by the large- size company's employers and high performanceemployers. (4) Young male workers have more negative attitude toward a change ofoccupation than young female ones. (5) Young female workers think their private living hours are more importantthan young male ones. (6) Elder workers (25-35 age) have more positive attitudes toward snperiorfigures, self-development programs, human relations at their work place thanyounger workers (18-25 age). (7) Employers support more strongly philosophy of traditional Japanese management systems than young workers.